DIGITAL MARKETING DAN MEMBANGUN BRANDING DI MASA PANDEMI COVID-19 - Sofyan Mufti Prasetiyo; Dini Hadiati; Fajar Aji Pangestu Utomo; Setyo Handoko (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Digital marketing has been proven as an effective way to expand brand reach and increase sales figures. In the digital era like today, marketing trends continue to grow along with the development of increasingly sophisticated technology with the presence of the internet. In Indonesia, digital marketing has developed greatly considering that internet users in Indonesia are increasing. Currently, the high number of social media users in Indonesia has had quite an effective impact on boosting exposure to digital marketing campaigns in Indonesia. This certainly attracts the attention of business people. Now, almost all business people do not hesitate to market their products or services via social media. Digital marketing increased during the 2019 Covid pandemic. One of the impacts of the COVID-19 pandemic is a downturn in the world of business and the economy. Thus marketers and entrepreneurs must find alternative solutions to be able to market their products or services to consumers. Business people optimize digital marketing and branding as a means of communication with their target consumers. This is certainly a very effective choice during this pandemic. The results of the research in this article are twofold. 1) Digital marketing and digital branding analysis. 2) Describe digital marketing and digital branding in the midst of the COVID 19 pandemic.